2012
DOI: 10.2224/sbp.2012.40.3.369
|View full text |Cite
|
Sign up to set email alerts
|

The Sweet Smell of the Requester: Vanilla, Camphor, and Foot-in-the-Door

Abstract: Several researchers have shown that odors affect human behavior. However, odors have not been studied in the context of specific compliance without pressure. Specifically, the impact of the odor worn by a requester during the foot-in-the-door procedure has not been documented. To address this issue, an experiment was carried out in an ecological setting. Using the foot-in-the-door procedure, a well-known technique for increasing the likelihood that a person will comply with one's request, the requester was pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Thus, this result should be interpreted with caution. In fact, some research suggest that pleasant odors indeed may improve performances in a cognitive task (Baron & Bronfen, 1994;Ho & Spence, 2005), provoke helping behavior (Baron, 1997) or even increase compliance (Saint-Bauzel & Fointiat, 2012). Also, Jacquemier (2001) has shown that releasing flowers scents in underground stations enhances positively the users' stations perceptions, and the intentions to take the underground.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, this result should be interpreted with caution. In fact, some research suggest that pleasant odors indeed may improve performances in a cognitive task (Baron & Bronfen, 1994;Ho & Spence, 2005), provoke helping behavior (Baron, 1997) or even increase compliance (Saint-Bauzel & Fointiat, 2012). Also, Jacquemier (2001) has shown that releasing flowers scents in underground stations enhances positively the users' stations perceptions, and the intentions to take the underground.…”
Section: Discussionmentioning
confidence: 99%
“…More speculatively, it has been suggested that those companies wishing to reduce their customer's shock when sending out large bills should consider scenting them with vanilla as this might help to relieve stress and anxiety 50 . Elsewhere it was found that those individuals scented with vanilla, but not with, camphor, were more likely to be successful in 'foot-in-the-door'-type procedures 51 . The scent of vanilla is apparently particularly popular amongst North American real-estate brokers 52 .…”
Section: The World's Most Liked Smellmentioning
confidence: 99%
“…For the last five decades, this social influence strategy has been well-documented and empirically validated (Dillard et al, 1984;Burger, 1999;Pascual and Guéguen, 2005). It still spikes interest among researchers (Dolinski, 2009(Dolinski, , 2012Fointiat and Saint-Bauzel, 2010;Saint-Bauzel and Fointiat, 2012;Pascual et al, 2013;Gamian-Wilk et al, 2018). The two metaanalyses conducted on FITD show a moderate effect (Beaman et al, 1983;Dillard et al, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…Performing or agreeing to perform a preliminary low cost behavior (e.g., preparatory request) increases the probability of performing a second more costly one (e.g., target request). Therefore, answering a short questionnaire on consumer habits (preparatory behavior) increases the probability that you will accept to have a team of surveyors in your home for 2 h (Freedman and Fraser, 1966), and even giving trivial information increases the probability of helping others (Saint-Bauzel and Fointiat, 2012). For the last five decades, this social influence strategy has been well-documented and empirically validated (Dillard et al, 1984;Burger, 1999;Pascual and Guéguen, 2005).…”
Section: Introductionmentioning
confidence: 99%